Influence of Dielectric Medium on a Cyano Containing Mesogenic Compound- A Statistical Study Based on Quantum Mechanics and Intermolecular Forces - Sahaya Baskaran, G.; Lakshmi Praveen, P.; P. Ojha, Durga (Asian Journal of Chemistry, 2012)
A statistical study based on quantum mechanics and intermolecular forces has been carried out for a cyano containing mesogenic compound 5-(trans-4-heptylcyclohexyl)-2-(4-cyanophenyl)pyrimidine with respect to translatory and orientational motions. The evaluation of net atomic charges and dipole moment at each atomic centre has been carried out through the complete neglect differential overlap (CNDO/2) method. The modified Rayleigh-Schrodinger perturbation method along with multicentered-multipole expansion method has been employed to evaluate long-range intermolecular interactions, while a '6-exp' potential function has been assumed for short-range interactions. The total interaction energy values obtained through these computations were used to calculate the probability of each configuration in a dielectric medium (i.e., non-interacting and non-mesogenic solvent, benzene) at room temperature (300 K) using the Maxwell-Boltzmann formula. An attempt has been made to study the influence of dielectric medium on a mesogenic compound in the light of configurational probabilities of dimer complexes. On the basis of different modes of interaction energy calculations, all probable geometrical arrangements of pairs have been considered. The most favorable configuration of pairing has been obtained.